2009
DOI: 10.1038/gt.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

PML has a predictive role in tumor cell permissiveness to interferon-sensitive oncolytic viruses

Abstract: The oncotropic phenotypes of several viruses correlate with tumor-associated deficiencies within interferon (IFN) signaling pathways. This observation formed the conceptual basis for developing oncolytic viruses deleted for viral proteins that inhibit the host IFN-dependent antiviral response, such as herpes simplex virus type-1 infected cell protein-0 (ICP0) and vesicular stomatitis virus matrix protein. Many viruses have evolved means to disrupt promyelocytic leukemia protein (PML) nuclear bodies. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection. Consistent with these results, decreased expression of PML in a variety of tumour cells correlates with increased permissiveness for ICP0-null mutant HSV-1 replication, and disruption of ND10 by expression of the PML-RAR fusion protein also increases replication of the mutant virus (Sobol et al, 2009). Given that PML is expressed as a complex family of proteins as a result of both alternative splicing and post-translational modification (Jensen et al, 2001), we set out to determine which PML isoforms are (D)Immunofluorescence data were quantified, presented and analysed statistically as described for Fig.…”
Section: Discussionsupporting
confidence: 66%
“…We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection. Consistent with these results, decreased expression of PML in a variety of tumour cells correlates with increased permissiveness for ICP0-null mutant HSV-1 replication, and disruption of ND10 by expression of the PML-RAR fusion protein also increases replication of the mutant virus (Sobol et al, 2009). Given that PML is expressed as a complex family of proteins as a result of both alternative splicing and post-translational modification (Jensen et al, 2001), we set out to determine which PML isoforms are (D)Immunofluorescence data were quantified, presented and analysed statistically as described for Fig.…”
Section: Discussionsupporting
confidence: 66%
“…A recent study has reported an increase in tumor cell sensitivity to VSV induced by downregulation of the MX1 gene ( 105 ). The PML gene has also been implicated in resistance to OVs ( 106 ), whereas the role of other ISGs largely remains unexplored.…”
Section: Mechanisms Of Resistance To Type I Ifnsmentioning
confidence: 99%
“…HSV-1 mutants defective for the production of ICP0 protein provide an attractive alternative to the MGH2 vector backbone. ICP0-deficient vectors are impaired for growth at low MOI in most cell lines, while replication preferentially occurs in certain tumor cell lines [22, 23, 37]. Moreover, Hummel and colleagues have reported that an HSV-1 double mutant lacking VP16 and ICP0 protein expression replicates efficiently in a variety of tumor cells derived from prostate, lung, colon, and mammary carcinomas with evidence of oncolytic activity in animal models [24].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mutants lacking ICP0 protein are impaired for growth at low multiplicity of infection (MOI) in most cell lines [20], while vigorous replication has been observed in tumor cell lines such as U2OS osteosarcoma cells [21, 22]. It has recently been demonstrated that other tumor cell lines enhance the replication of ICP0-deficient vectors, and an HSV-1 mutant lacking ICP0 protein expression was shown to increase survival in a mouse breast adenocarcinoma model [23, 24]. The tumor cell-specific replication of ICP0-deficient HSV suggests that this mutant backbone may represent a new class of oHSV vector useful for treatment of GBM.…”
Section: Introductionmentioning
confidence: 99%